Temperature dependence of some properties of star-branched polymers in confined space. A Monte Carlo study - Romiszowski, P. (Condensed Matter Physics, 2002)
A simulation study of star-branched molecules with 3 arms was performed in a space confined between two parallel repulsive walls, which were at the distance d apart. The simulations were performed for chains on a simple cubic lattice. The chains consisted of N = 49 , 100 and 199 beads. During the simulations the solvent quality has been varied by means of changing the segment-segment interactions. Also the thickness of a layer between the walls has been changed. The results show that there is a coil-to-globule transition. The transition temperature does not depend on the confinement. However, the scaling exponents of the radius of gyration of the chains are sensitive to value d .